Menelusuri karya intelektual Sayyid Usmanbin Yahya dalam bidang fikih - Muhammad Noupal (State Institute of Islamic Studies (IAIN) Salatiga, 2011)
Sayyid Usman, a Hadrami scholar in the 19th and early 20th century was very controversial. He was themufty of Batavia as well as advisor to the Netherlands East Indies. Especially as a mufty, Sayyid Usmanwas becoming a reference to the people who requested for a ruling of law. Supported by his ownprinting litographyc, Sayyid Usman was able to convey his views dan ideas widely through the publica-tion of books and treatises. The books produced by Sayyid Usman specialized in the field of Islamic lawor fiqh which refers to social jurisprudence. While related to the fiqh of worship, more concise and verysimple. Among his works in the field of law, the book of al-Qawanin al-Shar’iyyah is a very importantwork. This book contains a methodological description on how to take a legal decision (fatwa). Asadmitted, the purpose of writing al-Qawanin is a guide for prince and a judge of religion, especially inlegal decisions based on Ahlu Sunna sect.